Efficacy and safety of the long-term Vagus Nerve Stimulation: Preliminary report in adult patients with drug-resistant focal epilepsy - Barreto-Acevedo, Elliot (2019)
Objective: To report the efficacy and long-term safety of the Vagus Nerve Stimulation (VNS), in a series of adult patients with drug-resistant focal epilepsy, treated in a hospital of Peruâ€™s Social Security System. Methods: Data of the Adult Epilepsy Unit at Edgardo Rebagliati National Hospital, from June 2016 to June 2019, were reviewed in order to identify patients who had been implanted with VNS. Frequency of seizures and antiepileptic drugs (AED), prior to implantation with VNS, at 3 and 6 months, and at the end of the follow-up period were recorded, as were the average percentage change in the frequency of seizures, response rates of â‰¥ 50%, â‰¥75%, and changes in AED and adverse effects. Results: Five patients with drug-resistant multifocal epilepsy who were implanted with VNS for not being candidates to resective epilepsy surgery were identified. The average age was 20.6 years old. The average duration of follow-up from the implant was 21 months and the average percentage in the reduction of the seizure frequency at 3, and 6 months, and at the end of the follow-up period (21 months), was 24%, 45% and 69%, respectively. The response rates of â‰¥ 50% and â‰¥ 75% were 80% and 40%. There was a partial reduction of AED in only 1 patient. The main adverse effect was hoarseness. Conclusions: The experience with VNS, reported for the first time in Peru, demonstrates its efficacy as palliative therapy, and good safety profile in adults with drug-resistant multifocal epilepsy. The effectiveness is significantly higher with sustained long-term stimulation.